Review and Meta-Analyses of TAAR1 Expression in the Immune System and Cancers - Fleischer, Lisa M.; Somaiya, Rachana D.; Miller, Gregory M. (Frontiers in Pharmacology, 2018)
Since its discovery in 2001, the major focus of TAAR1 research has been on its role in monoaminergic regulation, drug-induced reward and psychiatric conditions. More recently, TAAR1 expression and functionality in immune system regulation and immune cell activation has become a topic of emerging interest. Here, we review the immunologically-relevant TAAR1 literature and incorporate open-source expression and cancer survival data meta-analyses. We provide strong evidence for TAAR1 expression and discuss its regulation in a spectrum of immune cell types as well as in numerous cancers. We reveal connections and logical directions for further study of TAAR1 in immunological function, and its potential role as a mediator or modulator of immune dysregulation, immunological effects of psychostimulant drugs of abuse, and cancer progression.